2008
DOI: 10.1021/ja800142t
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Phase States of Self-Assembled Monolayers on Pentacene Growth and Thin-Film Transistor Characteristics

Abstract: To investigate the effects of the phase state (ordered or disordered) of self-assembled monolayers (SAMs) on the growth mode of pentacene films and the performance of organic thin-film transistors (OTFTs), we deposited pentacene molecules on SAMs of octadecyltrichlorosilane (ODTS) with different alkyl-chain orientations at various substrate temperatures (30, 60, and 90 degrees C). We found that the SAM phase state played an important role in both cases. Pentacene films grown on relatively highly ordered SAMs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
277
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 225 publications
(291 citation statements)
references
References 62 publications
14
277
0
Order By: Relevance
“…The soft and rubbery characteristics of the TSB3 surface facilitate the lateral diffusion of pentacene molecules 32,34 . Similarly, previous studies revealed higher D values for pentacene admolecules on disordered SAMs, which have mobile alkyl chains and soft surface, than on ordered SAMs 11,12 . This enhanced surface diffusion contributes to the self-ordering of pentacene with far fewer grain boundaries in the first seeding layer.…”
Section: Article Nature Communications | Doi: 101038/ncomms5752supporting
confidence: 71%
See 1 more Smart Citation
“…The soft and rubbery characteristics of the TSB3 surface facilitate the lateral diffusion of pentacene molecules 32,34 . Similarly, previous studies revealed higher D values for pentacene admolecules on disordered SAMs, which have mobile alkyl chains and soft surface, than on ordered SAMs 11,12 . This enhanced surface diffusion contributes to the self-ordering of pentacene with far fewer grain boundaries in the first seeding layer.…”
Section: Article Nature Communications | Doi: 101038/ncomms5752supporting
confidence: 71%
“…By adding an interfacial layer, such as self-assembled monolayers (SAMs) and polymeric materials, between the semiconductor and the underlying substrate, the interface properties can be controlled effectively for favourable mesoscale/nanoscale ordering of the organic semiconducting layer 5 . It is generally known that the surface of well-ordered SAMs promotes the two-dimensional (2D) growth of vacuum-deposited organic semiconductor thin films and improves the crystallinity; the surface of disordered SAMs is believed to degrade the film quality by reducing the interaction between the surface and admolecules, inducing the threedimensional growth rather than the 2D growth 11,12 .…”
mentioning
confidence: 99%
“…Silicon oxide surface was treated with self-assembled monolayers of octadecyltrichlorosilane (OTS) for Cy-NDI and octadecyltrimethoxysilane (OTMS) for DMDCNQI in prior to the evaporation of the materials. 45,46 Cy-NDI and DMDCNQI were thermally deposited on the substrates with a thickness of 50 nm, where the evaporation was carried out under 10 −4 Pa for Cy-NDI, but 10 −3 Pa for DMDCNQI due to the high vapor pressure. 41 In order to fabricate transistors with top-contact configuration, the sourcedrain electrode was patterned with shadow masks by thermal deposition of Au (channel length L = 100 ÎŒm and channel width W = 1000 ÎŒm) onto the organic thin films.…”
Section: Methodsmentioning
confidence: 99%
“…Many groups have reported field-effect mobilities greater than 1 cm 2 /Vs for OFETs in which pentacene is used as the active layer. [1][2][3][4] The surface characteristics of the gate dielectric strongly influence the quality of the gate dielectric-semiconductor interface hence the device performance. [5][6][7] In the last decade, considerable effort has been devoted to the fabrication of OTFTs using organic gate dielectrics [8][9][10][11][12] for use as switching devices for flexible displays.…”
Section: Introductionmentioning
confidence: 99%